Travel to School and Housing Markets: A Case Study of Sheffield, England. (November 2013) - Ferrari, Ed; Green, Mark A
How children travel to school is at the centre of a complex set of interrelated issues with significant policy implications. This paper reviews the relation of patterns of travel to school to concerns about public health, school choice, urban form, and residential housing markets. The spatial relations between pupils' homes and the schools that they attend provides the basis of an analytical framework that links local neighbourhood characteristics, school performance, and house prices to the distance and mode of travel to school and the level of 'excess commuting' in the urban system. A unique analysis of several integrated micro-datasets from Sheffield, UK, suggests that, while there are high levels of excess commuting, there remains a complex interrelationship between housing and neighbourhood characteristics, school performance, and commuting patterns. There are differences between the pictures for primary schools and secondary schools. Policies aimed at promoting transport efficiency and those promoting school choice are likely to remain in tension.